MANAGEMENT OF THE AGRICULTURAL SECTOR SYSTEM BASED ON INNOVATIVE TECHNOLOGIES - Dosent, Mamadiyarov Dilshod Uralovich (Scholar Express Journals, 2024)
The article describes the achievements and disadvantages in the process of managing the agricultural sector based on innovative technologies and foreign experience in this area
Keywords: agro-industrial complex; innovative development; innovative news